DISTINGUISHING FEATURES OF CONCLUSION OF AN INTERNATIONAL FACTORING CONTRACT FROM AN INTERNATIONAL FOREITING CONTRACT - Ismailovna, Imamova Dilfuza (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The article considers legal aspects of the conclusion of international factoring and forfeiting agreements, which are important tools of foreign economic activity. The definition of the concept of factoring and forfeiting contract is reflected. Similarities and differences between these two financial instruments are analyzed, taking into account various criteria. Special attention is paid to the international legal regulation of these types of contracts. Recommendations on supplementing the Civil Code of the Republic of Uzbekistan with new provisions on forfeiting contract for the purpose of simplification of law enforcement practice and stimulation of international trade are offered.